Connecting the Dots: Comparing SPH Simulations and Synthetic Observations of Star-forming Clumps in Molecular Clouds - Ward, Rachel L. (My University, 2011)
The gravitational collapse of a giant molecular cloud produces localized dense regions, called clumps, within which low-mass star formation is believed to occur. Recent studies have shown that limitations of current observing techniques make it difficult to correctly identify and measure properties of these clumps that reflect the true nature of the star-forming regions. In order to make a direct comparison with observations, we produced synthetic column density maps and a spectral-line cube from the simulated collapse of a large 5000 solar mass molecular cloud. The synthetic observations provide us with the means to study the formation of star-forming clumps and cores in our simulation using methods typically used by observers. Since we also have the full 3D simulation, we are able to provide a direct comparison of `observed' and `real' star-forming objects, highlighting any discrepancies in their physical properties, including the fraction of cores which are gravitationally bound. We have accomplished this by studying the global properties of the star-forming objects, in addition to performing a direct correlation of individual objects to determine the error in the observed mass estimates. By correlating the clumps found in the simulation to those found in the synthetic observations, we find that the properties of objects derived from the spectral-line data cube were more representative of the true physical properties of the clumps, due to effects of projection greatly impacting the estimates of clump properties derived from two-dimensional column density maps.
Keywords: Star formation; Molecular Clouds; Simulations; Synthetic Observations; Stars, Interstellar Medium and the Galaxy; Stars, Interstellar Medium and the Galaxy